Kyai and His Family’s Criticism and Praise toward Santri at Pesantren - Badrudin, Ali; Sofyan, Akhmad; Salikin, Hairus; Muta'allim; Wijaya, Roma (KARSA Journal of Social and Islamic Culture, 2023)
The communication system in pesantren tends to be figurative. Kyai and his family often use figurative patterns to convey criticism and praise to Santri. This study describes the form, type, and function of criticism and praise of kyai and his family to santri. The theory used to explore criticism and praise is a descriptive and socio-pragmatic theory with the ethnographic method of communication. This research is qualitative. The method used in data collection is the participant observation method. The researchers observed conversations between kyai and their families with the santri, especially those involving criticism and praise. We conducted interviews with koai, pesantren families, and santri equipped with recording and note-taking techniques. The collected data was then reduced and classified based on categories. Subsequently, we transcribed the data in orthographic form and translated it into Indonesian. The results showed that there were two categories of speech in the pesantren environment, namely criticism, and praise; (1) The form of criticism of kyai and his family to santri are reprimands, command, satire, advice, and praise; (2) The forms of praise are motivation, praise, and reprimand. In the motivation and praise, speakers always use subtle, figurative, and direct sentences, while in the reprimand, speakers always praise the interlocutor by criticizing a third person.